Comprehensive Analysis of CDCAs Methylation and Immune Infiltrates in Hepatocellular Carcinoma - Wang, Yongkang; Yang, Yinfeng; Gao, Honglei; Ouyang, Ting; Zhang, Luyao; Hu, Jili; Hu, Sheng; Kan, Hongxing (Frontiers in Oncology, 2021)
Background As essential components of cycle growth, the cell division cycle-associated family genes (CDCAs) have crucial roles in the development and progression of cancers. However, little is known about the epigenetic mechanism of CDCAs in mediating phenotypic changes. Presently, we aimed to comprehensively explore the expression and prognosis of CDCAs with regard to methylation and immune infiltrates in hepatocellular carcinoma (HCC). Methods We first identified the differentially expressed genes (DEGs) between 19 different types of cancers (total of 7783 patients) and normal control samples using the RRA package in R and then constructed the weighted gene co-expressed and co-methylated network through the WGCNA package. Applying the clustering analysis, significant modules of DEGs including CDCAs were selected and their functional bioinformatics analyses were also performed. The correlation between the methylation levels of CDCAs and tumor immune infiltrates were analyzed through DiseaseMeth and TIMER. Finally, to assess the influence of CDCAs methylation on clinical prognosis, Kaplan-Meier and cox regression analysis was carried out. Result We successfully identified significant over-expression of CDCA1-3 and CDCA5-8 in HCC. Co-expressed and co-methylated networks revealed that there was a strong positive correlation between mRNA expression and methylation of CDCAs. Besides, CDCAs were enriched in immune functions regulating infiltrating immune cells in HCC. And the methylation states of CDCAs were strongly associated with tumor immunogenicity, e.g., low-methylation of CDCA1, CDCA2, and CDCA8 dramatically reduced the immune infiltrate levels of T cells and cytotoxic lymphocytes. Additionally, CDCA1-6 and CDCA8 with low-methylation levels significantly deteriorated the overall survival of patients in HCC. Conclusions All the results suggested a correlation between CDCAs methylation and immune infiltrating levels in HCC, providing the rationale for further investigating CDCAs methylation as a predictive biomarker for response to immunotherapy.